International Federation for Emergency Medicine model curriculum for medical student education in emergency medicine. Issue 10 (8th July 2010) - Hobgood, Cherri; Anantharaman, Venkataraman; Bandiera, Glen; Cameron, Peter; Halpern, Pinchas; Holliman, James; Jouriles, Nicholas; Kilroy, Darren; Mulligan, Terrence; Singer, Andrew; ,
Abstract : Currently, there is no internationally recognised, standard curriculum that defines the basic minimum standards for emergency medicine education. To address this, the International Federation for Emergency Medicine convened a committee of international experts in emergency medicine and international emergency medicine development to outline a global curriculum for medical students in emergency medicine. This curriculum document represents the consensus of recommendations by this committee. The curriculum is designed with a focus on the basic minimum emergency medicine educational content that any medical school should be delivering to its students during their undergraduate years of training. The content is relevant not just for communities with mature emergency medicine systems, but also for developing nations or for nations seeking to expand emergency medicine within current educational structures. It is anticipated that there will be wide variability in how this curriculum is implemented and taught, reflecting the existing educational milieu, the resources available and the goals of the institutions' educational leadership.